GLOBALIZATION AND ITS CHALLENGES - Ferreira Pantoja, Falckner (Revista Gênero e Interdisciplinaridade, 2023)
Globalization is the name given to the phenomenon of integration of the world space through technical advances in the communication and transport sectors. This process intensified with the advent of the Third Industrial Revolution, which saw an increase in international flows of capital, goods, people and information. This process is marked by the proliferation of transnational companies and the consolidation of financial capitalism, promoting profound changes in the international economic system and in the organization of work. In its current phase, new geographic networks were created, and there was an unprecedented expansion of the scales of information propagation and also of consumption. Despite this, globalization has not spread homogeneously across territories, placing part of the world’s population on the margins of this process. This work is a literature review.